AB0866 Sensorineural hearing loss in patients with ankylosing spondyitis: Is it an extra-articular feature of disease?. (23rd January 2014) - Barcelos, A.; Aguiar, R.; Cunha, I.; Ambrόsio, C.; Neves, A.; Azevedo, L.
Abstract : Background: Ankylosing Spondylitis (AS) is a chronic inflammatory disease of unknown aetiology. Sacroiliitis is the hallmark of AS, but peripheral joints and extra-articular structures may also be affected. There are two points of otological interest in AS patients: the possibility of sensorineural hearing loss (SNHL) due to long-term use of non-steroidal anti-inflammatory drugs and the disease may affect articular tissue in the middle ear and vascular structures owing to autoimmune reactions in the inner ear. Objectives: The aim of this investigation was to study the relationship between AS and hearing loss. Methods: This study compared 61 patients with AS (122 ears) with 46 age-matched controlls (92 ears). All subjects underwent to an audiologic evaluation that included puré-tone audiometry thresholds at octave frequencies of 250 to 8000Hz and impedance audiometry (tympanogram and static compliance). Results: The mean age of the patients was 45, 85 years (range 20-75 years) and in the controls group was 41, 48 years (range 25-55 years). Sensorineural hearing loss was found in 45 patients (73, 7%) that was bilateral in 31 patients and unilateral in eleven patients. There was no statistically significant difference between the two groups with respect to hearing levels at 250 -500Hz and 4000-8000Hz (p=0, 34). In AS group there was no correlation found between SNHL and age (p=0, 16). There was also no correlation found between SNHL and limitation in neck movement. (p=0, 17). Conclusions: Sensorineural hearing loss is common in AS patients as well in controls in this study. In opposite of what is described in literature, in our study SHNL was found as frequently in AS patients as in controls. Disclosure of Interest: None Declared